DISTORY: PENGEMBANGAN KAMUS DIGITAL SEJARAH BERBASIS VISUAL BASIC PADA MATERI KERAJAAN TARUMANEGARA - Muhammad Rofiul Alim (Universitas Negeri Malang, 2021)
The transformation of learning in the 21st century requires an adjustment between the development of science and technology. Learning sources are part of the learning system that is transformed from conventional learning sources into digital-based learning sources. Digital-based learning sources are considered more practical than conventional learning sources. Digital-based learning sources can be applied to history, which many students get bored easily when studying. Therefore, the aim of this study is to develop a digital-based learning source for history that makes it easier for students to study it. Digital History Dictionary (Distory) is an application of a digital-based learning source that has been developed based on learning requirement analysis. Distory also can make it easier for students to find and learn history. The main purpose of the development of Distory is an innovation of digital-based historical learning sources that is economical, practical, flexible, and appropriate with learning objectives. The research methodology used in the research and development of Distory, was based on Sugiyono’s research model, namely: (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) design revision; (6) small class trials; (7) product revision; (8) large class trials; (9) product revision; and (10) mass production. Distory is validated by experts as a basis for product improvement before field trials are carried out. Small and large class trials were carried out on the students of Madrasah Aliyah Negeri (MAN) Batu. The results of the validation of media experts, small class trials, and large class trials were 85 percent, 88.75 percent, and 89 percent, respectively. Based on these results, the development of Distory can be categorized as very decent and ready to be implemented.